AWS Certified Developer (Associate) - Garner, Nick (Pearson IT Certification, 2019)
14+ Hours of Video One Line Sell More than 14 hours of video instruction preparing the viewer for the AWS Associate Level Certified Developer exam by discussing and demonstrating the services included in the published blueprint of the exam, including AWS CLI & SDK, IAM, VPC, EC2, Route53 DNS, S3, DynamoDB, etc. Overview This course, "AWS Certified Developer Complete Video Course" focuses on the role-based certification, AWS Developer Associate. According to Amazon, "this exam validates proficiency in developing, deploying, and debugging cloud-based applications using AWS." Amazon Web Services currently has over 130 individual services available for use. Each service falls into an overarching category such as compute, storage, database, networking, etc. The AWS Developer Associate focuses on those services and concepts relevant to developers using, or intending to use, AWS services to create their applications. This course covers the published blueprint for the Associate level Certified Developer exam. It's important to note that this course is not intended to teach you to how program or develop applications. The goal is to help you understand the services that are available to run the applications you develop through live demonstration. Each lesson begins with a walk-through to provide an overview of the topic and then goes into demonstration mode. The majority of the demonstrations in this course are accomplished with a free AWS Trial Account so you can follow along. This course takes a lab-based approach to teaching you, which means we will focus on how to develop throughout the training so you can get some hands-on experience working in AWS. You will also learn about the objectives in the exam, but the emphasis is on doing so you can gain the experience needed to actually develop in AWS as well as pass the test. Each lesson has a lab-based exercise that walks you through concepts and also allows you to dive into a project. Lab files are included as downloads with the course so you can work alongside the author and work on projects." Nick Garner has co-founded an IoT company that runs entirely on AWS infrastructure that he manages. He has certifications in AWS, CEH, CISSP and 2 CCIEs (routing/switching and security). He works with Amazon Web Services design on a daily basis, particularly with respect to extending enterprise services into cloud service providers such as Amazon AWS, Microsoft Azure, and Google Compute. Topics include: Module ...